Water Protection in Makhdoom Muhammad Hashim Thattvi Teachings - Dr Abdul Majeed Dars,; Dr. Mufti Muhammad Sahibdad, (Al Manhal Research Journal, 2024)
This paper reflects the principles of saving and protecting water from environmental pollution according to the Islamic teachings. Of course, it highlights those principles as presented in Makhdoom Muhammad Hashim Thattvi teachings. Also, it expresses Makhdoom Thattvi’s significant contributions to Islamic knowledge, especially in Quranic interpretation, Hadith, and Fiqh, while promoting Shariah and eradicating un-Islamic practices in Sindh. His efforts strengthened the beliefs of Ahl-e-Sunnah and played a crucial role in the religious revival of Sindh during his time. In Islamic teachings, water is considered one of the greatest blessings given to man, and life springs from it. Preservation of water is, therefore, a responsibility that can hardly be overemphasized. Makhdoom Muhammad Hashim Thattvi, a renowned Sufi and scholar of Sindh, strongly laid emphasis on water conservation and environmental protection in his literature. This paper examines his teachings in the present challenges and looks forward to finding solutions to problems of water scarcity, pollution, and sustainable development. The study illustrates how the teachings of Islam, coupled with Thattvi's teachings, contribute to reducing environmental issues in today's world.